Preliminary indicators of the use of lesson study as a teaching practice capable of enabling an inclusive perspective in higher education - Oliveira, Jáima Pinheiro de [UNESP]; Bracken, Seán; Nakano, Natália [UNESP] (FapUNIFESP (SciELO), 2021)
This study approached the Lesson Study strategy as a support for planning academic activities of teachers who intend to adopt or contribute to the adoption of an inclusive perspective in Higher Education. The general objective of this study was to describe preliminary indicators of the use of the Lesson Study as a teaching practice capable of enabling an inclusive perspective, in the context of Higher Education. Specifically, we aim to: a) identify strategies by student with and without markers (social, linguistic, ethnic, neuromotor, among others) as suggestions for the teaching-learning process with an inclusive perspective, and b) compare these strategies and discuss them from the point of view of the teaching practice aspects tested in this analysis. With a predominantly qualitative approach, this research was characterized as descriptive and the investigation instruments used for data collection consisted of interviews, observation and field notes. Three university professors and a group of twelve students, four of them with markers (social, linguistic, ethnic, neuromotor, among others), and eight of them without any makers participated in this analysis. The results allowed to highlight four specific indicators of the Lesson Study and 26 types of strategies indicated by the students (with and without markers) as suggestions for support during teaching practices. It was observed that those provided by students without markers did not differ much from those presented by the students with markers, except in specific situations, such as those pointed out by the deaf student. The obtained data contributed to the discussions on the existing policies and guidelines generated in the University itself and, in particular, the analysis provided professional improvement of the involved professors, in addition to the indication of possibilities of this improvement in relation to the other professors who are concerned with the adoption of actions with inclusive education perspectives.
Indicadores preliminares do uso da lesson study como prática de ensino capaz de viabilizar uma perspectiva inclusiva na educação superior
Keywords: Higher education; Lesson study; School inclusion; Special education; Students